2017
DOI: 10.14238/sp18.6.2017.492-7
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Masalah Perilaku pada Remaja dengan Irritable Bowel Syndrome

Abstract: Latar belakang. Irritable bowel syndrome (IBS) merupakan nyeri perut berulang pada remaja yang paling banyak terjadi. Oleh karena itu, IBS akan menimbulkan gangguan perilaku yang serius pada remaja. Tujuan. Menganalisis hubungan antara masalah perilaku dengan IBS pada remaja. Metode. Penelitian potong lintang semua siswa SMA Nurul Iman. Pencatatan dilakukan meliputi karakteristik umum dan pemeriksaan fisis. Selanjutnya dilakukan uji Rome III (irritable bowel syndrome) dan PSC-17 (masalah perilaku). Analisis st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
(11 reference statements)
1
3
0
1
Order By: Relevance
“…Female gender had an odds ratio of 2.8 for risk of IBS compared to male gender, though the result was not significantly different. Two other Indonesian studies in Jakarta 3 and Palembang, South Sumatera, 12 by reported similar findings. This result may be due to varying populations and unequal gender ratio of the subjects analyzed.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Female gender had an odds ratio of 2.8 for risk of IBS compared to male gender, though the result was not significantly different. Two other Indonesian studies in Jakarta 3 and Palembang, South Sumatera, 12 by reported similar findings. This result may be due to varying populations and unequal gender ratio of the subjects analyzed.…”
Section: Discussionsupporting
confidence: 66%
“…However, a school-based study in Jakarta reported a significant association between corporal punishment and IBS (P=0.034). 3 Other school-based studies in Palembang, South Sumatera 12 and Korea 13 also found that psychosocial factors such as behavior problems and stress were connected to IBS. A mental health review of the school environment revealed many stressors that can affect children's mental health.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies have identified several factors associated with the incidence of IBS in adolescents, including history of abuse, type of food, and diet. 10,11 Of 8 Natalita's study found 40 subjects (62.5%) suffering from sleep disturbances using the SDSC questionnaire, with the most frequent type being sleep-wake disorder (25%). Based on the examination performed in this study, there were 42 subjects (65.6%) who suffered from sleep disorders using the SDSC questionnaire, with 71.4% sensitivity and 54.5% specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Hal tersebut berkaitan dengan ketersediaan nutrisi dan pelayanan kesehatan, serta kualitas kesehatan yang sehat. 14 Faktor risiko yang tidak memiliki hubungan bermakna dengan kejadian sakit perut berulang pada penelitian kami adalah usia, jenis kelamin, tingkat penghasilan orang tua, riwayat sakit perut berulang pada keluarga kandung. Keberagaman kelompok usia yang diteliti, definisi atau kriteria diagnosis, dan jenis kuesioner yang digunakan menyebabkan perbedaan hasil penelitian kami dengan penelitian lainnya terhadap faktor yang mempengaruhi kejadian sakit perut berulang.…”
Section: Hasilunclassified